Employee Safety Motivation: perspectives and measures on the basis of the Self-Determination theory - Mariani, Marco Giovanni; Soldà, Bianca Lara; Curcuruto, Matteo (La Medicina del Lavoro, 2015)
Background: There is a growing body of literature demonstrating that employee’s safety behaviour is largely influenced by their motivation to work safely. The Self-Determination Theory, which proposes a multidimensional conceptualization of motivation, is now established in various domains of the academic field (Healthcare, Education, Psychopathology, Organizations, Sport etc.). However, there are few publications concerning its use in the analysis of motivation in a safety context, where it constitutes a new topic of study. Objective: The aim of this study was to develop and validate the Italian version of the Self-Determined Safety Motivation Scale and analyze the psychometric properties of the scale in terms of construct validity. Methods: The research involved 387 Italian employees from three companies, who occupied medium-low levels in the organizational hierarchy. Results: A good level of psychometric properties was shown. Conclusion: The Italian version of the Self-Determined Safety Motivation Scale is a reliable and valid instrument to assess safety motivation.